Students’ performance of BSIE and BSHE in drawing subjects in the University of Eastern Philippines - ANTONIETO L. ADORA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The purpose of the performance was to compare the Drawing grades of BSIE and BSHE majors. The study’s specific aims were to (1) ascertain the socio-demographic profile of respondents in terms of age, sex, type of high school graduate, parental educational attainment, and learning resources at home; (2) ascertain the level of performance of respondents in their Drawing subject; and (3) test the significance of any relationship between the respondents’ profile and their performance in the Drawing subject.Methodology: The research was done in Northern Samar, Philippines, at the University of Eastern Philippines in University Town. In this study, we employed a descriptive correlation strategy. The sample’s socioeconomic characteristics were determined through a questionnaire administered as part of the data collection process for the study. We also obtained the respondents’ ratings/grades in Drawing from the University Registrar’s Office to use as a basis for quantifying their performance in that course.Findings: The majority of participants in the study performed well in the Drawing subject, according to the results. Students learned to analyze data and apply principles to concepts presented through the project method, which encouraged an exploratory approach. The demonstrative method, in which the instructor shows students how to do something for them to learn, understand, and appreciate what they’re being taught, was also employed.Implications/Novelty: The student values drawing as highly as they do industrial arts and home economics. This study has considered several factors to enhance students’ performance in the Drawing subject area, as there is much to be done to enhance learning outcomes.